FACTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN KREDIT, SERTA PENGARUHNYA TERHADAP KINERJA BANK - Iman Permana Ardi Kelana, 11.42.02.0042 (Students Journal of Economic and Management, 2013)
Banking institution has important role for economic growth which one of it as an intermediary institution between party that has excess fund and party that needs fund. From its role as a financial intermediary, bank with healthy financial performance is needed to make intermediary function running well. Intermediary problems is not only happen in domestic bank but also foreign bank with speculative activity that cause Rupiahâs fluctuation. Since banks are the major source of financing especially in South East Asia, the level of credit growth is an important policy variable for it indicates how efficiently banks perform their intermediary roles of collecting savings and allocating fund. This research has a purpose to provide empirical evident about factors that affect credit growth, also influences to performance banks. Variables that tested are credit sensitivity to interest rate, credit sensitivity to inflation, credit sensitivity to GDP, credit growth, and performance banks. The samples consist of 25 banks. The statistic method used to test on the research hypothesis is regression analysis. The result show that credit sensitivity to interest rate, credit sensitivity to inflation and credit sensitivity to GDP can predict credit growth and credit growth can predict performance banks. Key words : credit sensitivity to interest rate, credit sensitivity to inflation, credit sensitivity to GDP, credit growth, and performance banks